2014
DOI: 10.1103/physrevd.90.114035
|View full text |Cite
|
Sign up to set email alerts
|

D-wave heavy-light mesons from QCD sum rules

Abstract: We study the D-wavecs heavy meson doublets ð1 − ; 2 − Þ and ð2 − ; 3 − Þ using the method of QCD sum rule in the framework of heavy quark effective theory. Choosing the same threshold values ω c around 2.7 Gev, we calculate the masses of the 1 − and 3 − states. They are m D Ã s1 ¼ 2.81 AE 0.10 GeV and m D Ã s3 ¼ 2.85AE 0.08 GeV, consistent with the newly observed D Ã s1 ð2860Þ and D Ã s3 ð2860Þ states by LHCb. The masses of their 2 − partners are calculated to be 2.82 AE 0.10 and 2.81 AE 0.08 GeV. The mass spl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 41 publications
0
39
1
Order By: Relevance
“…First, we specify the input parameters in our calculation. = 2810 MeV [6], M D s2 = 2820 MeV [6], and…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we specify the input parameters in our calculation. = 2810 MeV [6], M D s2 = 2820 MeV [6], and…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…The LHCb Collaboration also announced that this was the first observation of a heavy flavored spin-3 resonance and the first time that any spin-3 particle had been seen to be produced in B decays [1]. Although D s J (2860) had been reported a e-mail: lfgan@nudt.edu.cn before by the BaBar Collaboration [3,4], it has inspired a lot of new interest in studying the spectroscopy ofcs mesons and the relevant processes [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…[299,300,301,302,49]. It can also be applied in the framework of heavy quark effective theory [303,304,305] to study heavy mesons [306,307,308,309,310,311,312,313,314,315,316,317] and heavy baryons [318,319,320,321,322,323,324,325,326,327,328,329].…”
Section: A Short Introduction To the Methods Of Qcd Sum Rulementioning
confidence: 99%
“…More studies on heavy mesons and baryons using this scheme can be found in Refs. [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80], and others using the method of QCD sum rules but not in HQET can be found in Refs. [81][82][83][84][85].…”
Section: Introductionmentioning
confidence: 99%